Placental Pathology and Blood Pressure’s Level in Women with Hypertensive Disorders in Pregnancy - Vassiliki Krielessi; Nikos Papantoniou; Ioannis Papageorgiou; Ioannis Chatzipapas; Efstathios Manios; Nikos Zakopoulos; Aris Antsaklis (Obstetrics and Gynecology International)
Objective. The aim of this study was to investigate the extent of placental lesions associated with blood pressure (BP) levels in pregnancies complicated by hypertension. Methods. 55 singleton pregnancies complicated by mild hypertension were recruited and compared to 55 pregnancies complicated by severe hypertension. The histological assessment was carried out with regard to the following aspects: vessels number/field of vision, infarction, villous fibrinoid necrosis, villous hypermaturity, avascular villi, calcifications, lymphohistiocytic villitis, and thickened vessels. Statistical analysis was performed by SPSS. Results. All placental lesions were observed more often in the severe hypertension group. Vessels number was significantly decreased, and infarction and villous fibrinoid necrosis were significantly increased in the placentas of the severe hypertension group compared to the mild hypertension group (𝑃<0.001). Conclusion. This study supports that the extent of placental lesions in hypertensive pregnancies is correlated with hypertension level and so highlights blood pressure level as a mirror of placental function.